Aerodynamic Analysis of a Localized Flexible Airfoil at Low Reynolds Numbers (Communications in Computational Physics, 2020)
A localized flexible airfoil at low Reynolds numbers is modeled and theaerodynamic performance is analyzed numerically. With characteristic based splitscheme, a fluid solver for two dimensional incompressible Navier-Stokes equations isdeveloped under the ALE framework, coupled with the theory of shallow arch, whichis approximated by Galerkin method. Further, the interactions between the unsteadyflow and the shallow arch are studied in detail. In particular, the effect of the self-excited vibration of the structure on aerodynamic performance of the airfoil is investigated deeply at various angles of attack. The results show that the lift-to-drag ratiohas been increased greatly compared with the rigid airfoil. Finally, the relationshipbetween the self-excited vibration and the evolution of the flow is analyzed using FFTtools.